Modus Penipuan Investasi Non-Fungible Token (NFT) Dalam Blockchain Solana - Margaret, Monica; Yusuf, Mizu Athaya (Dinasti Research, 2025)
The focus of this research is to identify the factors that make investors victims of fraud in the context of NFT investments. The theoretical foundation used in this study is the Lifestyle Exposure Theory, which helps in understanding how investors' lifestyles influence their risk of being scammed. This research employs a qualitative approach with a case study method through interviews to gain an in-depth understanding of fraudulent patterns in NFT projects. Data analysis is conducted using a descriptive approach to thoroughly illustrate and explain the phenomenon, providing insights into the factors that make investors vulnerable to fraud in the context of NFT investments. Lack of self-control and minimal verification of information make investors more susceptible to fraudulent schemes. The habitual factors identified above demonstrate their role as victims in fraud schemes, a concept known as Participating Victims.